Characterization of an evaluation success model of an IS project, focused on stakeholders - Ribeiro, Pedro Abreu (2018)
Typically, we measure the success of an Information Technology project through time, budget and quality. However, with the advance of years, we found that stakeholders have also something to say about success evaluation. Each stakeholder has an impact, its own interests and expectations about the project development. Therefore, what for some can be considered a success, for others can be considered a failure, because each one has a different perspective on the same project. This short paper proposes a flexible success evaluation model for an Information Technology project, called Success Breakdown Structure (SBS). In this model, the various stakeholders present in a project are presented, as well as their success assessment criteria over three different visions: after the completion of the project, after a few months and last, after a few years. From the obtained results, we can conclude that the evaluation of a project success is not concern of project managers only, but is transversal to all stakeholders.